2005
DOI: 10.1017/s002211200500710x
|View full text |Cite
|
Sign up to set email alerts
|

Wall imprint of turbulent structures and heat transfer in multiple impinging jet arrays

Abstract: Thermal imprint and heat transfer on the target surface in multiple impinging jet arrays have been investigated in conjunction with flow pattern and large-scale eddy structure. Surface temperature was measured with liquid crystal thermography (LCT) in a range of jet configurations with hexagonal and in-line orifice arrangements for different combinations of distances between the orifices s/D m = 2-6 and between the orifice plate and the impingement surface H/D m = 3-10 (where D m is the orifice diameter). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 25 publications
4
34
0
Order By: Relevance
“…LEON F. G. GEERS 18) focused on both pressure and velocity distribution characteristics, which were similar to the water cooling condition. Kercher and Tabakoff 19) presented the spatially-averaged surface heat transfer coefficients beneath an array of impinging jets with an in-line arrangement, whereas the results demonstrated that the Reynolds number and the streamwise/spanwise hole spacing were the most important parameters which affected all magnitudes of the spatial-averaged heat transfer coefficients.…”
Section: Local Heat Transfer Characteristics Of Multi Jet Impingementmentioning
confidence: 99%
“…LEON F. G. GEERS 18) focused on both pressure and velocity distribution characteristics, which were similar to the water cooling condition. Kercher and Tabakoff 19) presented the spatially-averaged surface heat transfer coefficients beneath an array of impinging jets with an in-line arrangement, whereas the results demonstrated that the Reynolds number and the streamwise/spanwise hole spacing were the most important parameters which affected all magnitudes of the spatial-averaged heat transfer coefficients.…”
Section: Local Heat Transfer Characteristics Of Multi Jet Impingementmentioning
confidence: 99%
“…The contours of mean velocity magnitude on the plane1 and 2 are visualized. Compared to the instantaneous flow, for the narrow spacing case, we can clearly mention the notable flow feature due to jet-jet interaction: early breakdown of potential core and excessive reduction outer edge of jet occurs before the jet impingement; large-scale flow has been pointed out as 'fountain' in previous literatures (Geers, Hanjalić, and Tummers, 2006;Weigand and Spring, 2011) are formed around the center of the impinging wall(r = 0), regardless of the jet-to-jet spacing.…”
Section: Fig 8 Contour Of Instantaneous Velocity Magnitudementioning
confidence: 69%
“…Thus in order to overcome the shortcoming of single impinging jet (SIJ), i.e., the occurrence of both inhomogeneous heat distribution on the wall and the narrow heating area, multiple impinging jets (MIJ) are generally introduced in industrial applications. Thus far it is well-known that each jet of MIJ interacts with each other, producing the complex flow field (Geers, Hanjalić, and Tummers, 2006;Weigand and Spring, 2011). In addition, the heat transfer performance is significantly influenced with their interaction.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, 7 mm nozzle spacing, and 5.0 mm jet-to-target distance were set by optimizing the cooling parameters. Many studies [7][8][9] had been focused on the flow field and heat transfer of multiple air jet arrays, of which the pressure and velocity distribution characteristics are similar to the water cooling condition. The flow pattern includes stagnation region, decelerated flow, recirculating flow and vortex.…”
Section: Experimental Investigation Of High-temperature Steel Plate Cmentioning
confidence: 99%